Proses Rekruitmen Pimpinan Birokrasi Pemerintah Daerah di Kabupaten Sleman dan Kota Parepare - ZULCHAIDIR ZULCHAIDIR (Universitas Muhammadiyah Yogyakarta, 2011)
This article describes about the recruitment process of bureaucracy leader in Sleman region andParepare city, Including several factors that influences the recruitment process.The methodology thatimplemented in this article is quantitative description with indepth interview and observation as themeans on collecting the data. This articles found that the recruitment process of bureaucracy inSleman district has implemented “competent testing system” in appointing goverment officials withalso considering the role of Baperjakat, while Parepare city has not implemented the testing systemyet. There is also several factors that influenced the recruitment process in Parepare which have beenidentified, which are: head of district commitments, personnels information, political interest and therole of academic institutions